Pemberdayaan Masyarakat Desa Rowokembu melalui Pelatihan Budikdamber dan Kebun Gizi sebagai Alternatif Pemenuhan Bahan Pangan - Harum Fadhilatunnur; M. Adil Danial Faza; M. Fakhrul Anam; Ita Vera; Noor A’fiana Desyani; Ayu Idha Mufidha; Nila Farizah; Yenny Zanubah Arifah; Sarah Puruhitaningrum; Dilla Ferawati (Institut Pertanian Bogor, 2022)
Rowokembu Village is one of villages in Wonopringgo Sub-district in Pekalongan Regency, Central Java. It has dense population with limited agricultural land. Vegetable garden and fish farming in bucket are among simpler yet effective strategies for this typical society. This program aimed to empower local community through training on vegetable garden and fish farming in bucket for the members of PKK (Pemberdayaan Kesejahteraan Keluarga) of Rowokembu. Training was given in the form of lecture and workshop. Changes on knowledge and perception was measured through pre-test and post-test. It was observed that the training managed to increase the knowledge, perception, and skills of the participants on developing vegetable garden and fish farming in bucket. The enthusiasm and participation, however, tend to decrease after training period. The fish showed high mortality rate presumably due to poor water condition, hot weather, the absence of aeration system, and improper feeding. The plants in the vegetable garden were attacked by pest. More intensive coaching/guidance was needed to ensure the sustainability of the program.